Macrophages and cardiac lesion in zebrafish: what can single-cell RNA sequencing reveal? - Luz, Rebeca Bosso dos Santos; Paula, André Guilherme Portela; Czaikovski, Andressa Pacheco; Nunes, Bruno Sime Ferreira; De Lima, Jordana Dinora; Paredes, Lais Cavalieri; Bastos, Thais Sibioni Berti; Richardson, Rebecca; Braga, Tarcio Teodoro (Frontiers in Cardiovascular Medicine, 2025)
Unlike mammals, zebrafish can regenerate their heart after cardiac insult. There are several ways to perform cardiac injury in zebrafish, but cryoinjury most closely resembles human myocardial infarction (MI). Studies demonstrated that macrophages are essential cells from the beginning to later stages of cardiac injury throughout the regenerative process in zebrafish. These cells have phenotypic plasticity; hence, overly sensitive techniques, such as single-cell RNA sequencing (scRNAseq), are essential for uncovering the phenotype needed for zebrafish cardiac injury regeneration, from inflammatory profile initiation to scar resolution. This technique enables the RNA sequencing of individual cells, thus generating clusters of cells with similar gene expression and allowing the study of a particular cell population. Therefore, in this review, we focused on discussing data obtained by scRNAseq of macrophages in the context of cardiac injury. We found that from 1 to 7 days post-injury (dpi), macrophages are present with inflammatory and reparative functions in either cryoinjury or ventricular resection. At 14 dpi, there were differences between the injury models, especially in the expression profile of inflammatory cytokines, and studies with later time points are needed to understand the gene expression that enrolls the collagen scar resorption dynamic.